Development of an extensible and scalable many : ImageObject viewer and add-on to web platform project - Lim, Chee Han. (2009)
NTU current e-learning website edventure is a very versatile and function filled website, however edventure lacks of functionality to grade image assignment with a user friendly interface. It is not very efficient for the instructor to grade the assignment separately outside of edventure then manually update the score in edventure. In this project, the Image Workbench software is proposed to aid instructor to manage, compare and grade the image assignment effectively.